Politics of Law Handling of Criminal Acts of Terrorism (Case Study In The District of Kudus) - Subkhan Subkhan; Widayati Widayati (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
Terrorism is a criminal act tremendous concern today's world, especially in Indonesia. Terrorism that occurred in Indonesia lately has associated ideological, historical and political as well as a dynamic part of the strategic environment at regional and global level. Terrorism is in fact an act which violates humanitarian and human rights as well as the proof that terror is the action of a very cruel and did not take into account, disregard and ignore the human values referred to in the second principle of Pancasila which became ideology Indonesian Nation humanity fair and civilized.In general, the legal political handling of criminal acts of terrorism in Indonesia as a strategic step taken by Government Regulation No. 1 of 2002 Post-Event 1 Bali bombings to face a precarious state that fills a legal vacuum. That then pass the regulation established as Act No. 15 of 2003 on the Eradication of Terrorism does not diminish its value as a legal norm, but in the development of the substance of legislation are assessed tend to be repressive and still found the articles that have not been able to cover the dynamics of the spread of ideology radical who became the mother of terrorism, and prevent acts of terrorism itself.Regulation alone is not appropriate presumably in combating terrorism, therefore we need other measures comprehensively, integral, planned and sustainable in the form of legal policy in order to cover the lack of normative law, by improving awareness and knowledge about the nationality and religious teachings properly , so that people can always be responsive and alert to the movement of radical groups that developed in the surrounding area.Keywords: Politics of Law; Handling, Management of Terrorism Crime.